Management of chronic lung diseases in Sudan and Tanzania: how ready are the country health systems? - Uzochukwu Egere; Elizabeth Shayo; Nyanda Ntinginya; Rashid Osman; Bandar Noory; Stella Mpagama; ElHafiz Hussein; Rachel Tolhurst; Angela Obasi; Kevin Mortimer; Asma El Sony; Miriam Taegtmeyer; et al. (BMC, 2021)
Abstract Background Chronic lung diseases (CLDs), responsible for 4 million deaths globally every year, are increasingly important in low- and middle-income countries where most of the global mortality due to CLDs currently occurs. As existing health systems in resource-poor contexts, especially sub-Saharan Africa (SSA), are not generally oriented to provide quality care for chronic diseases, a first step in re-imagining them is to critically consider readiness for service delivery across all aspects of the existing system. Methods We conducted a mixed-methods assessment of CLD service readiness in 18 purposively selected health facilities in two differing SSA health system contexts, Tanzania and Sudan. We used the World Health Organization's (WHO) Service Availability and Readiness Assessment checklist, qualitative interviews of key health system stakeholders, health facility registers review and assessed clinicians' capacity to manage CLD using patient vignettes. CLD service readiness was scored as a composite of availability of service-specific tracer items from the WHO service availability checklist in three domains: staff training and guidelines, diagnostics and equipment, and basic medicines. Qualitative data were analysed using the same domains. Results One health facility in Tanzania and five in Sudan, attained a CLD readiness score of ≥ 50 % for CLD care. Scores ranged from 14.9 % in a dispensary to 53.3 % in a health center in Tanzania, and from 36.4 to 86.4 % in Sudan. The least available tracer items across both countries were trained human resources and guidelines, and peak flow meters. Only two facilities had COPD guidelines. Patient vignette analysis revealed significant gaps in clinicians' capacity to manage CLD. Key informants identified low prioritization as key barrier to CLD care. Conclusions Gaps in service availability and readiness for CLD care in Tanzania and Sudan threaten attainment of universal health coverage in these settings. Detailed assessments by health systems researchers in discussion with stakeholders at all levels of the health system can identify critical blockages to reimagining CLD service provision with people-centered, integrated approaches at its heart.